Analysis of the Law of Joint Deformation for Grouted Mortise-Tenon Joint - Xiuren Yang; Fang Lin; Meiqun Huang (Advances in Civil Engineering)
This paper analyzes the law of joint deformation of grouted mortise-tenon joint with 1 : 1 prototype test in key working direction types under 38 working conditions of different joint types, tenon lengths, grouting ranges, grouting materials, and loading combinations for the prefabricated metro station. The deformation performance of the joint has also been compared. In addition, finite element models have been built, and the joint deformation stages are discussed. The influences on the law of joint deformation of different influencing factors have been discovered. The deformation development stages and the main deformation laws of each stage of the joints have also been obtained. Moreover, this paper also compares and analyzes the field test results and experimental results. The monitoring results show that the safety margin of joint deformation is sufficient during the whole construction process from the assembly to the completion of the station. The research results have great values for the joint design and calculation for the prefabricated metro station structure.